2004
DOI: 10.1016/s0002-9440(10)63284-1
|View full text |Cite
|
Sign up to set email alerts
|

BCL2 Translocation Defines a Unique Tumor Subset within the Germinal Center B-Cell-Like Diffuse Large B-Cell Lymphoma

Abstract: Gene expression profiling of diffuse large B-cell lymphoma (DLBCL) has revealed prognostically important subgroups: germinal center B-cell-like (GCB) DL-BCL, activated B cell-like (ABC) DLBCL, and primary mediastinal large B-cell lymphoma. The t(14;18)(q32; q21) has been reported previously to define a unique subset within the GCB-DLBCL. We evaluated for the translocation in 141 cases of DLBCL that were successfully gene expression profiled. Using a dual-probe fluorescence in situ hybridization assay, we detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
175
1
9

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(202 citation statements)
references
References 44 publications
17
175
1
9
Order By: Relevance
“…No statistical correlation was found between t(14;18) and BCL-2 protein expression, consistent with the results of some previous reports [17,19] but contrary to the findings of Barrans et al [20] . It is possible that BCL-2 expression is essential in early lymphomagenesis, but additional genetic abnormalities developing during tumor progression may abrogate this requirement.…”
Section: Discussionsupporting
confidence: 81%
“…No statistical correlation was found between t(14;18) and BCL-2 protein expression, consistent with the results of some previous reports [17,19] but contrary to the findings of Barrans et al [20] . It is possible that BCL-2 expression is essential in early lymphomagenesis, but additional genetic abnormalities developing during tumor progression may abrogate this requirement.…”
Section: Discussionsupporting
confidence: 81%
“…BCL2 may be the only gene preferentially mutated in the GCB subgroup because BCL2 translocations are known to be associated with GCB classification. 6 After BCL2, PIM1 showed the next highest number of potentially functional mutations, with non-synonymous single nucleotide variants in 17 out of 89 DLBCL samples. Notably, the single tumor with the most mutations in PIM1 (4 non-synonymous, 11 total) was of the ABC subtype.…”
Section: Discussionmentioning
confidence: 99%
“…This translocation is found in B20% of DLBCL, 5 most often in the GCB subtype of DLBCL. 6 Other mechanisms of BCL2 deregulation, more often observed in ABC DLBCLs, include amplification of the BCL2 gene or its transcriptional upregulation through constitutive activation of the nuclear factor-kB pathway. 7 Saito et al 8 reported that the BCL2 promoter can also be aberrantly hypermutated in DLBCL, which may prevent its inhibition by MIZ1 and BCL6.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35] More recently, it was demonstrated that inactivation of TP53 was associated with a particular GEP characterized notably by a decreased expression of TRAIL receptor-2. 26 Here, we delineated approximately 100 genes that distinguish DLBCL 9p21del .…”
Section: Discussionmentioning
confidence: 99%